A hybrid impedance control scheme for underwater welding robots with a passive foundation in the controller domain. (July 2017) - Kumar, Sunil; Rastogi, Vikas; Gupta, Pardeep
A hybrid impedance control scheme for the force and position control of an end-effector is presented in this paper. The interaction of the end-effector is controlled using a passive foundation with compensation gain. For obtaining the steady state, a proportional–integral–derivative controller is tuned with an impedance controller. The hybrid impedance controller is implemented on a terrestrial (ground) single-arm robot manipulator. The modeling is done by creating a bond graph model and efficacy is substantiated through simulation results. Further, the hybrid impedance control scheme is applied on a two-link flexible arm underwater robot manipulator for welding applications. Underwater conditions, such as hydrodynamic forces, buoyancy forces, and other disturbances, are considered in the modeling. During interaction, the minimum distance from the virtual wall is maintained. A simulation study is carried out, which reveals some effective stability of the system.